2022
DOI: 10.1002/acr.24844
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Use Among Medicare Beneficiaries With Knee Osteoarthritis: Prevalence and Correlates of Chronic Use

Abstract: Objective. To determine the prevalence of chronic and occasional opioid use and identify risk factors of opioid use among persons with knee osteoarthritis (OA).Methods. We used the Medicare Current Beneficiary Survey to select a knee OA cohort. We obtained data on demographics characteristics, marital status, comorbidities, insurance, and prescription medication coverage from survey data and linked Medicare claims. We included all prescribed medication records classified as opioid under the First Databank ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Opioid prescriptions for musculoskeletal pain have substantially contributed to opioid misuse in the US (46). Encouragingly, the prevalence of opioid use among those with knee OA has decreased each year from 2013 to 2016 (23), resulting in an estimated $20 billion decrease in lifetime knee opioid‐related costs. These data document the substantial impact that can be achieved by providing alternatives to opiates for knee OA pain management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opioid prescriptions for musculoskeletal pain have substantially contributed to opioid misuse in the US (46). Encouragingly, the prevalence of opioid use among those with knee OA has decreased each year from 2013 to 2016 (23), resulting in an estimated $20 billion decrease in lifetime knee opioid‐related costs. These data document the substantial impact that can be achieved by providing alternatives to opiates for knee OA pain management.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of data from the Medicare Current Beneficiary Survey (MCBS) found that prolonged opioid use among knee OA patients decreased from 12% in 2013 to 4% in 2016 (23). Despite these encouraging changes in opioid prescription practices, even a small proportion of SKOA patients in the US using opioids on a prolonged basis likely results in a large societal cost.…”
Section: Introductionmentioning
confidence: 99%
“…In the interim, since multiple findings point to a consistent negative influence of opioid usage on falls frequency in older adults [46,47] Yoshikawa., et al [48] imply caution is advised regarding the extended usage of opioids for purposes of alleviating knee osteoarthritis pain among older adults at high risk for falls [47,48]. This is indicated both before as well after any knee joint replacement surgery [49].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies results show similar findings in China, USA, and from six continents in over world. (13)(14)(15) In table 2 The findings show the majority of knee osteoarthritis patients do not routinely follow healthy lifestyle habits. For example, just 27.04% of patients said they regularly took responsibility for their health, and only 7.13% of patients said they regularly exercised.…”
Section: Discussionmentioning
confidence: 99%